Development of active neutron nondestructive assay system - Toh Yosuke; Ohzu Akira; Tsuchiya Harufumi; Furutaka Kazuyoshi; Kitatani Fumito; Komeda Masao; Maeda Makoto; Koizumi Mitsuo (EPJ Web of Conferences)
The assay of Special Nuclear Materials (SNM) and Minor Actinides (MA) in highly-radioactive nuclear materials poses a significant challenge for nuclear non-proliferation and security. No single nondestructive method can provide acceptable and practicable results for such materials. Therefore, the Japan Atomic Energy Agency (JAEA) and the Joint Research Centre of the European Commission (EC-JRC) have been developing an active neutron nondestructive assay (NDA) system. We utilize four different NDA techniques, namely Differential Die-Away Analysis (DDA), Prompt Gamma-ray Analysis (PGA), Neutron Resonance Transmission Analysis (NRTA) and Delayed Gamma-ray Analysis (DGA). These are promising and effective active neutron techniques especially for nuclear material accountancy. The techniques offer complementary information and can enhance the accuracy and reliability of the assay. The project focused on the development of the integrated NDA system for highly-radioactive materials. The new project, which started in 2022, aims to develop a compact NRTA system, because a more versatile system is required for nuclear security applications, and NRTA is considered as one of the most accurate NDA techniques to determine the amount of SNM and MA and is suitable for measurements of highly-radioactive nuclear materials.